Environmental Control of Single-Molecule Junction Evolution and Conductance: A Case Study of Expanded Pyridinium Wiring - Nováková Lachmanová, Štěpánka; Kolivoška, Viliam; Šebera, Jakub; Gasior, Jindřich; Mészáros, Gábor; Dupeyre, Grégory; Lainé, Philippe P; Hromadová, Magdaléna (Angewandte Chemie (International ed. in English), 2021)
Environmental control of single-molecule junction evolution and conductance was demonstrated for expanded pyridinium molecules by scanning tunneling microscopy break junction method and interpreted by quantum transport calculations including solvent molecules explicitly. Fully extended and highly conducting molecular junctions prevail in water environment as opposed to short and less conducting junctions formed in non-solvating mesitylene. A theoretical approach correctly models single-molecule conductance values considering the experimental junction length. Most pronounced difference in the molecular junction formation and conductance was identified for a molecule with the highest stabilization energy on the gold substrate confirming the importance of molecule-electrode interactions. Presented concept of tuning conductance through molecule-electrode interactions in the solvent-driven junctions can be used in the development of new molecular electronic devices.
Keywords: single-molecule conductance; solvent gating; molecular electronics; expanded pyridiniums; scanning tunneling microscopy